Rhodium-catalyzed enantioselective cyclopropanation of electron deficient alkenes - Wang, Hengbin (2013)
The rhodium-catalyzed reaction of electron-deficient alkenes with substituted aryldiazoacetates and vinyldiazoacetates results in highly stereoselective cyclopropanations. With adamantylglycine derived catalyst Rh(2)(S-TCPTAD)(4), high asymmetric induction (up to 98% ee) can be obtained with a range of substrates. Computational studies suggest that the reaction is facilitated by weak interaction between the carbenoid and the substrate carbonyl but subsequently proceeds via different pathways depending on the nature of the carbonyl.. Acrylates and acrylamides result in the formation of cyclopropanation products while the use of unsaturated aldehydes and ketones results in the formation of epoxides.